Research Progress of Traditional Chinese Medicine in the Treatment of Chronic Heart Failure - Pang, Jinhua; Hou, Jiejun (Journal of Contemporary Medical Practice, 2024)
Chronic heart failure is a relatively complex chronic disease that occurs on the basis of previous heart disease, characterized by a decrease in the hearts ability to pump blood and an insufficient output that cannot meet the bodys metabolic needs. In traditional Chinese medicine, chronic heart failure is believed to have a basic pathogenesis of deficiency with excess, primarily involving deficiency and yang deficiency of heart qi, which can affect the heart and even other organs and further worsen heart failure symptoms. Traditional Chinese medicine has achieved good results in the clinical treatment of chronic heart failure through the use of a holistic approach, becoming an indispensable force in the current treatment of chronic heart failure. This article expounds on the etiology, pathogenesis, and treatment principles and methods of chronic heart failure in traditional Chinese medicine based on classic texts, and briefly summarizes the methods of traditional Chinese medicine for treating chronic heart failure in recent years.